Pengaruh Pemberian Daun Kelor terhadap Produksi ASI di TPMB T. Sartika Kelurahan Sriamur Kecamatan Tambun Utara Bekasi Tahun 2023 - Tuti Sartika; Lia Idealistiana (Malahayati Nursing Journal, 2024)
ABSTRACT Low levels of exclusive breastfeeding can cause nutritional problems in toddlers. Efforts to overcome this, among others, by increasing the quality of breast milk. There are many ways that can be done to facilitate breast milk, including the consumption of Moringa leaves due to the presence of phytosterols which can increase milk production. This writing aims to determine the effect of giving Moringa leaves on breast milk production in Tpmb T. Sartika, Sriamur Village, North Tambun District, Bekasi, in 2023. This study used a quasy experimental one group pretest-posttest design. The population in this study were all postpartum mothers in the Sriamur sub-district, Tambun Utara sub-district, Bekasi. The number of respondents was 35 postpartum women, before and after being given Moringa leaves 35 people. Bivariate analysis using paired simple t test. The results of the study showed that before being given Moringa leaves, there were 28 mothers (80.0%) who were not fluent and after being given Moringa leaves, there were 31 mothers (88.6%) who were fluent. In conclusion, it was found that there was an effect of consumption of Moringa leaves on the smooth production of breast milk in postpartum mothers, where the results of the t test showed a sig. 0.000 0.05. It is suggested that future researchers can deepen their understanding of the mechanisms involved in the effect of consuming Moringa leaves on the smooth production of breast milk. Keywords: Moringa Leaves, Breast Milk Production  ABSTRAK Pemberian ASI eklusif yang masih rendah dapat menimbulkan masalah gizi pada balita. Upaya untuk menanggulanginya antara lain dengan meningkatkan dan kualitas ASI. Banyak cara yang dapat dilakukan untuk memperlancar ASI diantaranya konsumsi daun kelor karena adanya kandungan fitosterol yang dapat meningkatkan produksi ASI. Penulisan ini bertujuan mengetahui Pengaruh Pemberian Daun Kelor Terhadap Produksi ASI di TPMB T. Sartika Kelurahan Sriamur Kecamatan Tambun Utara Bekasi Tahun 2023. Penelitian ini menggunakan desain quasy eksperiment one group pretest-posttest design. Populasi dalam penelitian ini seluruh ibu nifas di wilayah kelurahan Sriamur kecamatan tambun utara bekasi. Jumlah responden 35 orang ibu nifas, sebelum dan sesudah diberikan daun kelor 35 orang. Analisis bivariat menggunakan uji paired simple t test. Hasil penelitian didapatkan produksi ASI sebelum diberikan daun kelor terdapat 28 ibu (80.0%) yang kurang lancar dan sesudah diberikan daun kelor terdapat 31 ibu (88,6%) yang lancar. Simpulan didapatkan bahwa ada pengaruh konsumsi daun kelor terhadap kelancaran produksi ASI pada ibu nifas, dimana hasil uji t menunjukkan nilai sig. 0,000 0,05. Disarankan untuk peneliti selanjutnya dapat memperdalam pemahaman tentang mekanisme yang terlibat dalam pengaruh konsumsi daun kelor terhadap kelancaran produksi ASI. Kata Kunci: Daun Kelor, Kelancaran ASI